Foreign Influence Factors Affecting Language Change - Bella Syifa Zulfia; Fajaria Nur Rahmah; Salsabila Yunita; Salwa Dzulhijjah Nanda Mahwan; Izzah Supeni (Peneliti.net, 2022)
Language change is the phenomenon by which permanent alterations are made in a language's features and use over time. In this study, the method used is a literature review, wherein in this study, researchers take references from various reading sources such as books, journals, and others. This study aims to determine the influence of foreign on language change in a region. Interaction with other persons who speak a different language causes language shift. Language contact refers to interactions between languages that can be caused by a variety of causes such as social, technological, cultural, political, and foreign influences, either intentionally or unintentionally. People's idea that a country should have more than one language is weakened by outside influence. Depending on their demands, they will eventually speak more than one language. The level of foreign influence on a society's language evolution is measured by language borrowing. The term